Failure analysis of dissimilar single-lap joints - F.A. Stuparu; D.A. Apostol; D.M. Constantinescu; M. Sandu; S. Sorohan (Fracture and Structural Integrity)
Single-lap joints made of aluminium and carbon fibre adherends of different thickness are tested to understand better the behaviour of such dissimilar joints. The overlap length and the thickness of the adhesive are kept constant. Local deformation fields are onitored by using the digital image correlation method. Peeling and shearing strains are investigated, emphasizing that peeling is important in the region where failure is initiated, towards an extremity of the overlap region. The use of only carbon fibre adherends is not recommended for a smaller thickness as an additional interface failure is produced and compromises the integrity of the lap joint. However, a dissimilar joint (aluminium-carbon) with smaller thickness adherends succeeds to maintain the stiffness of the assembly, but its strength is diminished. The obtained results are suggesting that a complete monitoring of the failure processes in the overlap region can be fully understood only if local deformation measurements are possible.